In the figure, LM = MN, QM = MR, ML ⊥ PQ, MN ⊥ PR, prove PQ = PR

Dear student

Regards

  • 6
Please find this answer

  • 1
GIVEN: LM=MN, QM=MR /_QLM=/_MNR=90
TO PROVE: PQ=PR
PROOF
IN TRIANGLE LQM AND TRIANGLE MNR,
LM=MN(GIVEN)
QM=MR(GIVEN)
/_QLM=/_MNR = 90
HENCE BY SAS THEY ARE CONGRUENT
AS THE TRIANGLES ARE CONGRUENT, PQ = PR BY C.P.C.T.



HOPE IT HELPS...:)
 
  • 0
LM=MN
OM=MR
angles QLM= angle MNR =90
SO TRIANGLE LQM IS CONGRUENT TO TRIANGLE MNR BY SAS 
BY CPCT PQ=PR
  • -1
What are you looking for?